Pelayanan Publik di Kantor Desa Bulontio Barat Kecamatan Sumalata Kabupaten Gorontalo Utara - Rafiq Madjham; Lucyane Djafar; Lukfiah I Radjak (Universitas Muhammadiyah Gorontalo, 2016)
This research implemented qualitative method with decriptive approach as the part of governmental research that aimed to determine the quality of public service in Bulontio Barat village office, Sumalata district, Gorontalo Utara regency. Souce of the data are taken from two sources they are primary data and secondary data. Based and the result of reserch it can be elaborated that 1) discipline of village official particulary head of the village is still far from the expectation and this brings impacts on working motivation of the officials, 2) the service is still oriented on the secretary of the village, 3) the service is low in term of promptness due to enadequate supporting facility, and 4) lack of the village officials` concern towards moral, ethics, and social problems. Penelitian ini menggunakan metode kualitatif melalui pendekatan deskriptif sebagai bagian dari penelitian pemerintahan, dengan tujuan untuk mengetahui kualitas pelayanan publik di kantor desa Bulontio Barat Kecamatan Sumalata Kabupaten gorontalo Utara. Sumber data penelitian memfungsikan dua sumber data yaitu sumber data primer dan sumber data sekunder. Berdasarkan hasil penelitian dapat diuraikan; 1) Disiplin aparat desa terutama kepala desa masih perlu ditingkatkan, 2) Pelayanan masih terpusat pada sekretaris desa, 3) Pelayanan masih lambat karena fasilitas penunjang pelayanan tidak memadai, 4) Perhatian aparat desa terhadap moral, etika dan masalah-masalah sosial masih kurang